Cytokine networks and their association with Helicobacter pylori infection in gastric carcinoma. Issue 4 (7th March 2017) - Bagheri, Vahid; Memar, Bahram; Momtazi, Amir Abbas; Sahebkar, Amirhossein; Gholamin, Mehran; Abbaszadegan, Mohammad Reza
Abstract : Cytokine networks as dynamic networks are pivotal aspects of tumor immunology, especially in gastric cancer (GC), in which infection, inflammation, and antitumor immunity are key elements of disease progression. In this review, we describe functional roles of well‐known GC‐modulatory cytokines, highlight the functions of cytokines with more recently described roles in GC, and emphasize the therapeutic potential of targeting the complex cytokine milieu. We also focus on the role of Helicobacter pylori (HP)‐induced inflammation in GC and discuss how HP‐induced chronic inflammation can lead to the induction of stem cell hyperplasia, morphological changes in gastric mucosa and GC development. Abstract : In this review, we describe functional roles of well‐known gastric cancer (GC)‐modulatory cytokines, highlight the functions of cytokines with more recently described roles in GC, and emphasize the therapeutic potential of targeting the complex cytokine milieu. We also focus on the role of Helicobacter pylori (HP)‐induced inflammation in GC and discuss how HP‐induced chronic inflammation can lead to GC.